High correlations in gene expression between paired umbilical cord blood and neonatal blood of healthy newborns on Guthrie cards. (December 2013) - Slaughter, Jaime; Wei, Changshuai; Korzeniewski, Steven J.; Lu, Qing; Beck, John S.; Khoo, Sok Kean; Brovont, Ariel; Maurer, Joel; Martin, Denny; Lenski, Madeleine; Paneth, Nigel
Abstract Objective: To examine the correlation in genes expressed in paired umbilical cord blood (UCB) and newborn blood (NB). Method: Total mRNA and mRNA of three gene sets (inflammatory, hypoxia, and thyroidal response) was assessed using microarray in UCB and NB spotted on Guthrie cards from 7 mother/infant pairs. Results: The average gene expression correlation between paired UCB and NB samples was 0.941 when all expressed genes were considered, and 0.949 for three selected gene sets. Conclusion: The high correlation of UCB and NB gene expression suggest that either source may be useful for examining gene expression in the perinatal period.